Tinjauan Yuridis Tentang Permohonan Pembatalan Perkawinan Dalam Konteks Perdata Islam (Studi Putusan Nomor 1993/Pdt.G/2022/PA.Tnk) - Kosasi, Amelia Nanda Putri; Baharudin, Baharudin; Satria, Indah (Jurnal Pro Justitia (JPJ), 2024)
Writing errors are discrepancies between correct writing rules and what should be written. Writing errors can also occur in various aspects, such as errors in basic words, affixes, prepositions, pronouns, numbers, numbers, abbreviations, punctuation and absorption elements. This can affect the understanding and interpretation of the text, so it is important to pay attention to the rules of correct writing. The problem in this research is what factors cause name changes in population documents (Study Decision Number: 195/Pdt.P/2023/PN.Tjk). And what are the judge's considerations in granting a name change decision in population documents (Decision Study Number: 195/Pdt.P/2023/PN.Tjk).